Development of deployable wing glider - Lim, Bi Fang. (2013)
This report will explore the development of a deployable wing mechanism for use in gliders of wingspan 1-1.5 metres. The wing will be stowed along the fuselage prior to launch and will be deployed to its desired location in flight. The objective of wing stowage is to achieve a higher height attainment during launch to maximize glide time. Stowing the wings alongside the fuselage reduces aerodynamic skin friction drag as well as lift induced drag due to the lowered exposed wing surface area. It also allows the glider to be launched with a launching mechanism capable of imparting greater force without structural limitation on the wings. Stowage of wings also offers space reduction in storage, which enables portability.